2020
DOI: 10.4103/jpbs.jpbs_159_20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insight into odontogenesis in hyperglycemic environment: A systematic review

Abstract: A BSTRACT Diabetes mellitus is an endocrinal disorder affecting worldwide and the disease incidence is rising alarmingly high. The effects of diabetes on tooth development are explored by limited studies and their molecular insights are very rarely studied. This systematic review is aimed to provide the best scientific literature source on the molecular insights into odontogenesis in hyperglycemic environment caused by diabetes mellitus or by maternal diabetes on the offspring. The lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Furthermore, epigenetic changes can alter the phenotype of the tooth organ without genetic alteration. [ 13 ]…”
Section: E Tiopathogenesis Of M Olar M Alformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, epigenetic changes can alter the phenotype of the tooth organ without genetic alteration. [ 13 ]…”
Section: E Tiopathogenesis Of M Olar M Alformationsmentioning
confidence: 99%
“…[ 23 ] Animal studies have shown that hyperglycemic environment affects the phenotype of resulting teeth by epigenetic alterations. [ 13 ]…”
Section: Olar M Alformations In V Arious S Ystemic D Iseasesmentioning
confidence: 99%
“…Also empirical studies have shown the presence of missing teeth as a new find in case of Type 2 diabetes. Nowadays diabetic patients are seen to have tooth loss which is twice that of other normal individuals.Sometimes hereditary inheritance of diabetes in children could also lead to early loss of teeth [22].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of periodontitis in diabetic individuals increases by three folds when compared to non diabetic individuals [16]. The uncontrolled diabetes and hyperglycemia [17] results in reduced defence mechanisms and higher chances of acquiring infection leading to periodontal disease. The deep pockets, severe gingival inflammation [18], rapid bone loss and periodontal abscess is commonly seen in diabetic individuals with poor oral hygiene.…”
Section: Introductionmentioning
confidence: 99%